Testing the Weak Form of Efficient Market Hypothesis and Causality Analysis in Colombian Food Supply Centers - Talero-Sarmiento, Leonardo Hernán; Lamos-Díaz, Henry; Garavito-Hernández, Edwin Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In Colombia, there are traditional food supply centers to trade agricultural products. Government institutions publish sale prices of these products in weekly reports. In order to determine the random characteristics of these price series and if there are relationships between the centers, we use a battery of six different tests to examine the weak form of efficient market hypothesis and the Granger causality test. For this, this work collected the historical weekly price of 28 agricultural products, taking into account six markets, during the first week of 2013 to the last week of 2017. The main results indicate that markets tend towards efficiency, however, the efficiency depends on the product traded. In addition, the centers in Manizales, Barranquilla and Villavicencio influence the prices of the Bogotá, Bucaramanga and Medellín markets.